O „prawniczych” znaczeniach terminu culpa w Kodeksie Teodozjusza - Jońca, Maciej (Vox Patrum, 2014)
The Latin term culpa on the legal ground is usually associated with responsibility for torts. Many of the contemporary works link this legal construction with Roman law, which till now is praised for its concision and clarity. Yet not all Roman sources present the clear dogmatic view on this point. Being permeated with rhetoric the Theodosian Code offers various meanings of this term, which considerably differ from the ideas elaborated by the classical Roman law. Nevertheless the code played substantial role in the process of development of law in the Medieval Europe.